Mechanical Properties of Self-Compacting Concrete Incorporating Palm Oil Fuel Ash (POFA) and Gypsum Powder as Partial Cement Replacement - Goh, Wan Inn; Yasmin, Ramli; Qadir Bux Alias, Imran Latif; Kamaruddin, Sufian (International Journal of Integrated Engineering, 2024)
This study investigates sustainable substitutions to Ordinary Portland Cement (OPC) in Malaysia's construction sector, aiming on the environmental impact instigated by greenhouse gas emissions. The research explores using 20% palm oil fuel ash (POFA) and 5% to 15% gypsum powder (GP) as partial cement replacements in self-compacting concrete (SCC). The study utilized cement, sand, coarse aggregate, POFA, and GP. POFA was sourced from a palm oil plant, processed into fine powder, and combined with gypsum powder as a partial cement replacement. The SCC mixtures followed a specific ratio of 1:2:1.7 for cement, sand, and coarse aggregate, with varying percentages of POFA and GP. The objective was to achieve a compressive strength of 30 MPa with SCC densities between 2000–2600 kg/m³.  Concrete cubes (100 mm x 100 mm x 100 mm) were cast for compressive strength testing, and cylinders (100 mm x 200 mm) were used to measure the modulus of elasticity and Poisson’s ratio. The samples were cured in water for 7 and 28 days. The specimens were subjected to compressive strength tests using standardized testing machines. Cylinders were tested to measure the deformation under load, following guidelines to assess stiffness and elastic properties. The significance of this research lies in its contribution to sustainable construction by offering alternative materials to OPC towards reduce carbon emissions. By incorporating waste materials such as POFA and GP, the study not only addresses environmental concerns however also suggests practical solutions to decrease cement demand. This approach can help reduce the environmental footprint of the construction industry and encourage the recycling of agricultural by-products. This paper advances the understanding of how waste materials can be integrated into concrete production, proposing a viable alternative to traditional methods with significant environmental and industrial benefits.